2019
DOI: 10.1111/jgh.14808
|View full text |Cite
|
Sign up to set email alerts
|

Dietary emulsifier polysorbate‐80‐induced small‐intestinal vulnerability to indomethacin‐induced lesions via dysbiosis

Abstract: Background and AimDietary emulsifiers are widely used in processed foods and officially approved as safe for intake. However, recent studies have demonstrated that some emulsifiers alter the colonic microbiota, leading to colonic low‐grade inflammation, in mice. The effect of dietary emulsifiers on small‐intestinal microbiota, which is important for gut immunity, has not been studied. We aimed to investigate the effect of a representative dietary emulsifier, polysorbate‐80 (P80), on the small‐intestinal microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…B. Chassaing et al demonstrated that mice treated with 1% P80 dissolved in drinking water for 12 weeks had low-grade inflammation, obesity/metabolic syndrome, and colitis ( 5 ). Moreover, H. Furuhashi et al also found 1% P80 could induce small intestine vulnerability to indomethacin-induced lesions ( 54 ). Thus, we also chose 1% P80 as the intervention concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. Chassaing et al demonstrated that mice treated with 1% P80 dissolved in drinking water for 12 weeks had low-grade inflammation, obesity/metabolic syndrome, and colitis ( 5 ). Moreover, H. Furuhashi et al also found 1% P80 could induce small intestine vulnerability to indomethacin-induced lesions ( 54 ). Thus, we also chose 1% P80 as the intervention concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Mice from the P80 group were exposed to P80 dissolved in sterilized water (1.0% [wt/vol]), whereas the control water group was supplied with sterilized water without P80. The dose was chosen based on a previous study ( 5 , 54 ). Female mice in the two groups were mated with male mice after 3 weeks of predisposing with sterilized water or P80 dissolved in sterilized water and checked daily.…”
Section: Methodsmentioning
confidence: 99%
“…High fat diet aggravates indomethacin-induced small intestinal damage in mice via intestinal dysbiosis, increases gene expression of interleukin (IL)-17A in the intestine and augments intestinal permeability ( Sugimura et al., 2019 ). A dietary emulsifier, polysorbate 80, exacerbates indomethacin-induced small-intestinal lesions via intestinal dysbiosis and increases protein expression of IL-1 β in the small intestine ( Furuhashi et al., 2019 ). A possible mechanism by which indomethacin can cause the translocation of luminal bacteria from the lumen into the mucosa is by altering the content of sugars and lipids in the glycocalyx layer of the mucosa ( Basivireddy et al., 2005 ).…”
Section: Impact Of Nsaids On Gut Microbiota Composition and Metabolicmentioning
confidence: 99%
“…Secondary endpoints of the FADiets study include changes in bacterial diversity and metabolic activity, gut inflammation and glucose metabolism. Alterations to the composition of the gut microbiota have been observed in animal models following exposure to emulsifiers (Table ), with some reporting increased Proteobacteria (Chassaing et al ; Furuhashi et al ). We will monitor for any differences in faecal bacterial community structure between habitual diet, and the high‐ and low‐emulsifier diets by Illumina MiSeq sequencing of the V1–V2 regions of bacterial 16S rRNA genes isolated from participant faecal samples.…”
Section: Objectives Of the Mecnut Emulsifier Project And The Fadiets mentioning
confidence: 99%